Perceptions of economically active people who had to do remote work during the COVID19 pandemic due to having a comorbidity: a qualitative study - Granero, Mariano; Viti, María; Colombo, Malena; Mozeluk, Natalia; Terrasa, Sergio (Revista del Hospital Italiano de Buenos Aires, 2022)
IntroductionPeople with some pre-existing conditions are more likely to have a severe form of COVID-19. In Argentina, people with any of these comorbidities performed remote and differentiated work compared to their peers. This strategy is known as shielding and has heterogeneous results, since although it prevents infections it can have some impact on people's experiences and health.MethodsExploratory research through a qualitative design based on semi-structured interviews.Results21 interviews were conducted. The concepts were organized in thematic axes of analysis. As the main findings, we identified that the general health of the people worsened during the pandemic despite performing differentiated work, and that during the period explored, emerged both unhealthy habits and positive coping strategies. Regarding work, negative feelings predominated over positives.ConclusionThe implementation of shielding is insufficient as the only measure for the preservation of the health of people at higher risk of developing severe forms of COVID-19.
Keywords: COVID-19; lockdown; remote work; shielding